Effects of social contexts on overweight and normal-weight children’s food intake - Salvy, Sarah-Jeanne (2007)
This study investigates the effects of peer influence on the food intake of overweight and normal-weight children. A mixed factorial design was employed, with children’s weight status (overweight vs. normal-weight) as a between-subjects factor, and social context (alone vs. group) as a within-subjects factor. A total of 32 children (n=17 overweight and n=15 normal-weight) between the ages of 6–10 years participated in this study. Findings from the random regression model indicated that overweight children ate more when alone than when in the presence of other youth, while in contrast normal-weight ate slightly more with others than they did when alone. Therefore, social context differentially impacts the eating behavior of overweight and normal-weight children. This study underscores differences in responses to the social environment between overweight and non-overweight youths, and suggests that social involvement may be an important tool in treatment and prevention programs for overweight and obesity.